2016
DOI: 10.1002/bio.3137
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence properties of annealed natural quartz after beta irradiation

Abstract: Here we investigated the effects of annealing, heating rate and fading (after annealing at 800 °C) on the thermoluminescence (TL) glow curves of natural quartz (NQ). All of the samples were annealed at different temperatures between 100 °C and 800 °C and then irradiated with a beta dose of about 34 Gray (Gy), in order to determine the effects of annealing treatments on TL peaks of natural quartz. TL glow curves of the samples were recorded. It was observed that the intensities of TL peaks were strongly sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…It is performed to erase the effects of previous irradiation, minimize the background signals, increase the sensitivity of the dosimeter, and obtain the highest reproducibility [22]. Some researchers investigated the effects of annealing on the TL properties of natural dosimetric materials [9,[23][24][25][26]. They concluded that pre-irradiation annealing at higher temperatures causes a huge increase in sensitivity in a TL sample and best reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…It is performed to erase the effects of previous irradiation, minimize the background signals, increase the sensitivity of the dosimeter, and obtain the highest reproducibility [22]. Some researchers investigated the effects of annealing on the TL properties of natural dosimetric materials [9,[23][24][25][26]. They concluded that pre-irradiation annealing at higher temperatures causes a huge increase in sensitivity in a TL sample and best reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…Among these mineral groups, natural clay is a significant member of hydrous aluminum silicates family. [4,5] In the past few decades, research on radiation-induced defects in minerals has gained significance. Thermoluminescence (TL) is a valuable technique employed to understand mechanisms of trapped electron capture and release resulting from the interaction of radiation with existing defects in the material lattice.…”
Section: Introductionmentioning
confidence: 99%
“…curves from various forms of quartz exhibit great differences in shape [3][4][5]. Many investigations on quartz have been performed about its different properties [1,[6][7][8][9][10][11]. Some of the different studies about TL and OSL methods by using quartz samples are presented below:…”
Section: Introductionmentioning
confidence: 99%
“…A number of optical properties of a natural quartz that are related to the presence of electron traps having an optical depth of about 3 eV below the conduction band were described by Huntley and et al [12], the effects of annealing, heating rate and fading (after annealing at 800°C) on the TL glow curves of natural quartz were investigated by Yüksel et al [6], the use of TL method to distinguish between burned and unburned soil samples were investigated using quartz samples obtained from soil by Rengers et al [13], the study of OSL dating of coarse-grain fluvial quartz using single-aliquot protocols on sediments was investigated by Fuchs and Lang [14], and in order to refine the OSL age of the last earthquake on the Dheshir fault in Central Iran, quartz samples were used by Fattahi et al [15].…”
Section: Introductionmentioning
confidence: 99%